Tradisi Tahfizh al-Qur`an Lansia di Pondok Tahfizh Ma’had An-Nur Sungai Tanang Kec. Banuhampu Kab. Agam - Adeliana Putri; Hardivizon Hardivizon; Zulhamdani Zulhamdani (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2023)
This study aims to analyze the response of elderly Qur'an memorizers to the Qur'an memorization activities at Ma'had An-Nur Islamic Boarding School in Agam Regency. The research focuses on the motivation of the elderly participants in engaging in Qur'an memorization, the implementation of Qur'an memorization among the elderly, and the attitude changes experienced by elderly participants after engaging in Qur'an memorization. The research method employed is qualitative with a case study design. Data were collected through observations and in-depth interviews with twelve key informants. The study finds that the motivation of the elderly participants in joining the Qur'an memorization activities at Ma'had An-Nur Islamic Boarding School varies. Some participants are motivated by religious reasons, aiming to draw closer to Allah through Qur'an memorization, while others seek rewards and Allah's pleasure in the afterlife. The implementation of Qur'an memorization among the elderly is carried out using methods that are suitable for the participants' abilities and health conditions. Methods such as "wahdah," "tikrar," "sima'i," and "tasmi'" are employed to facilitate the memorization process. After engaging in the Qur'an memorization activities, the elderly participants undergo positive attitude changes. They feel more serene, peaceful, and harmonious in their daily lives. Inner calmness, harmonious living, and a stronger belief in Allah are the changes experienced within themselves. Some participants exhibit a strong learning attitude, making efforts to improve their deficiencies in Qur'an memorization.